Potential Political Conflict in the 2024 Presidential Election (Conflict Theory Study) - Gunawan, Indra; Bahari, Yohanes (Universitas Tanjungpura, 2024)
This research discusses the potential for political conflict in the 2024 presidential election from the perspective of conflict theory. The conflict perspective used is according to the views of Karl Marx and Ralf Dahrendorf. The approach used in this research is qualitative research with a literature study method which discusses potential conflicts that will occur. Conflicts that will occur, quoted from Kompas (Firda Cynthia Anggrainy, 2023). one pair of presidential candidates who they consider to be unconstitutional. The results of this research show that there is potential for political conflict in the 2024 presidential election. There is potential for political conflict in the 2024 presidential election. According to Karl Max, conflict occurs based on the class gap factor. In this political phenomenon, classes are divided into two, the ruling class and the ordinary people. According to Ralf Dahrendorf, conflict occurs based on differences in interests of groups with interests. In the potential political conflict in the 2024 presidential election, it will be very easy for conflicts of interest to arise based on each presidential candidate and vice presidential candidate. Conflict is seen as the result of social inequality and differences in interests between individuals or groups. Such conflicts can play an important role in changing political agendas, resolving social problems, and creating long-term changes in society. However, conflict can also threaten social stability and worsen social integration.